Biến đổi khí hậu và ảnh hưởng của biến đổi khí hậu tới nông nghiệp - Tài liệu dùng cho cán bộ địa phương các cấp của Việt Nam - Luu NQ; Pham TS; Le DH; Le, Van Hai; Nguyen TTT; Vu HL; Ngo DM; Bui Tan Yen; Dinh TKD; Sebastian, Leocadio S. (2015)
Understanding the impacts of climate change on agriculture, associated landscapes and natural resources in general is crucial if local development efforts are to be tailored towards addressing the impacts of climate change. Simplification of scientific concepts can help local planners at different level to introduce and then mainstream strategies that have factored in the impacts from climate change. The brochure is written in Vietnamese for the benefit local partners and technical persons who speak and read Vietnamese language only.